Environmental Health and Gram Panchayat Members of Western Maharashtra, India - Yugantara R Kadam; Anuradha J Samant; Alka D Gore (Medsci Publications, 2012)
Background The purpose of environmental health is to create and maintain ecological conditions that will promote health and thus prevent disease. Gram Panchayat is a local government agency at village level. As community leaders, Gram Panchayat members (elected members of  Gram Panchayat) have more responsibility towards maintaining environmental health. Their awareness, attitude and practices regarding environmental health will determine village environment. Method: It is a cross-sectional study conducted in villages from talukas (administrative areas) of Kolhapur District. All Gram Panchayat members of six villages from three talukas were administered Self designed questionnaire. Results In awareness 41.3% members scored above 75% and in attitude and practice 71.73% and 67.39% members scored above 50% respectively. Only 6 (13.04%) members scored <50% in awareness. Awareness, attitude & practices were independent of age, sex, experience, post & distance from urban area. Members' awareness improves attitude and practices regarding environmental health. Gram Swachhata Abhiyan (Rural Sanitation Drive) that helps in improving awareness. Conclusion By improving environmental health awareness of Gram Panchayat members it is possible to improve attitude & practices.